Photo-Deposition of Ag Metal Particles on Ni-Doped TiO2 for Photocatalytic Application. (September 2017) - Elahifard, Mohammad Reza; Meidanshahi, Reza Vatan
Ni-doped TiO2 and Ag-deposited@Ni-doped TiO2 photocatalysts were prepared using the co-precipitation technique and characterised using X-ray powder diffraction, scanning electron microscopy and Brunauer–Emmett-Teller analysis. Our results confirmed the presence of Ni atoms in the TiO2 bulk structure and Ag° metal particles deposited on the surface. The Ni impurity generates defect midgap states in the TiO2 band structure, providing visible light (VL) absorption, which are responsible for photocatalytic activity under VL conditions. Against this advantage, Ni changes the indirect band gap of pure anatase to the direct band gap which may dramatically suppress the photocatalytic activity of Ni-doped TiO2 . Moreover, Ni may provide a centre of electron–hole (e–h) recombination which enhances the negative effect of Ni impurity on TiO2 photo-efficiency. These drawbacks were overcome by deposition of Ag° on the Ni-doped TiO2 which sinks the photo-excited electrons, quenching e–h recombination. This improvement yields three times more photo-efficiency in the decolourisation of Acid Blue 92. Although Ag@Ni-doped anatase shows a higher adsorption constant ( K ads ) than Ag@Ni-doped rutile, both catalysts surprisingly present the same rate constant ( k ).